Character Education Management as a Strategy for the Holistic Character Formation of Madrasah Students - Yuliani, Dwi; Asra, Muhammad; Zakariah, M. Askari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Character education is a fundamental aspect of the national education system that aims to shape students not only to excel academically, but also to have good attitudes, behavior, and morals. This study aims to analyze the implementation of character education management at MTs Al Mawaddah Warrahmah Kolaka and its impact on the formation of positive attitudes and behavior of seventh-grade students. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion, while data validity was tested using triangulation of sources, methods, and time. The results of the study indicate that the implementation of character education management at MTs Al Mawaddah Warrahmah Kolaka runs systematically through four management functions, namely planning, organizing, implementing, and evaluating. Planning is carried out in a participatory manner and is integrated into the Madrasah Work Plan and dormitory program. Organization is demonstrated through a clear division of roles between the madrasah principal, teachers, and dormitory supervisors. The implementation of character education is carried out through the integration of values in learning, educator role models, and daily habits. Evaluation is carried out continuously using an educational, academic, and dormitory approach. The implementation of character education management has a positive impact on improving students' discipline, religiosity, responsibility, and social behavior. This study concludes that integrated and sustainable character education management is effective in shaping students' character holistically.